I hereby claim:
- I am akiomik on github.
- I am akiomik (https://keybase.io/akiomik) on keybase.
- I have a public key ASDOSsrhwIXhzWFVQAIouvDYDHBGcISMBlECAzuazqcZfAo
To claim this, I am signing this object:
val NUM_LETTERS = 25 | |
implicit class RichChar(c: Char) { | |
def shiftLetter(i: Int): Char = { | |
if (c.isLetter) { | |
val (a, z) = if (c.isLower) ('a', 'z') else ('A', 'Z') | |
val n = i % NUM_LETTERS | |
(((c + n) % z % a) + a).toChar | |
} else { | |
c |
I hereby claim:
To claim this, I am signing this object:
cask :v1 => 'coredatautil' do | |
version '1.5.8' | |
sha256 '6e158ee215cde14582191804abc965b38db6f911fb22068631c80313fe0b90a8' | |
url 'https://github.com/yepher/CoreDataUtility/releases/download/1.5_8/CoreDataUtil.app.zip' | |
name 'CoreDataUtility' | |
homepage 'https://github.com/yepher/CoreDataUtility/releases' | |
license :unknown # todo: change license and remove this comment; ':unknown' is a machine-generated placeholder | |
app '' |
Change the plugin path of /usr/local/opt/cocos2d-x/bin/cocos2d.ini
.
53c53
< plugins=../plugins
---
> plugins=/usr/local/opt/cocos2d-x/tools/cocos2d-console/plugins
case class Calc(f: Int => Int, g: Int => Int, i: Int = 1) { | |
def calc: Int = (f compose g)(i) | |
} | |
object Calc { | |
def apply(f: Int => Int, g: Int => Int): Calc = new Calc(f, g) | |
} | |
// case class | |
val c1 = new Calc(_ * 10, _ + 10) |
import shapeless._ | |
import shapeless.Nat._ | |
import shapeless.ops._ | |
import shapeless.ops.nat._ | |
trait FizzBuzz[N <: Nat] { | |
type R3 <: Nat | |
type R5 <: Nat | |
def ti: ToInt[N] |
case class Calc(f: Int => Int, g: Int => Int, i: Int = 1) {
def calc: Int = (f compose g)(i)
}
object Calc {
def apply(f: Int => Int, g: Int => Int): Calc = new Calc(f, g)
}
sukoというパズルの適当なソルバを書いたので簡単なベンチマークを取ってみた。
問題は2014/01/06のmetro紙より。
new scala.testing.Benchmark {
replicate' :: Int -> a -> [a] | |
replicate' n x | |
| n <= 0 = [] | |
| otherwise = x : replicate' (n - 1) x | |
take' :; Int -> [a] -> [a] | |
take' n _ | |
| n <= 0 = [] | |
take' _ [] = [] | |
take' n (x : xs) = x : take' (n - 1) xs |